Rewriting logic and its applications : 11th International Workshop, WRLA 2016, held as a satellite event of ETAPS, Eindhoven, The Netherlands, April 2-3, 2016, Revised selected papers /: 11th International Workshop, WRLA 2016, held as a satellite event of ETAPS, Eindhoven, The Netherlands, April 2-3, 2016, Revised selected papers. (2016) - Unknown
No abstract available